Fetal growth profiles of macrosomic and non‐macrosomic infants of women with pregestational or gestational diabetes. (11th March 2013) - Hammoud, N. M.; Visser, G. H. A.; Peters, S. A. E.; Graatsma, E. M.; Pistorius, L.; de Valk, H. W.
ABSTRACT Objective To assess fetal growth profiles in an unselected group of pregnant women with either Type‐1 diabetes (DM1), Type‐2 diabetes (DM2) or gestational diabetes (GDM), with emphasis on intergroup differences and development of disproportionate fetal growth and macrosomia. Methods Second‐ and third‐trimester longitudinal ultrasound measurements of fetal growth were made in 77 women with DM1, 68 women with DM2 and in 99 women with GDM. Altogether 897 ultrasound examinations were performed and 145 uncomplicated pregnancies with 843 ultrasound examinations were included as controls. Ultrasound data included head circumference (HC), abdominal circumference (AC), femur length (FL) and HC/AC ratio. Results The AC, but not HC and FL, evolved differently in diabetic pregnancies, with a smaller AC in early pregnancy and larger AC at term (significant for DM1 and DM2). The most striking differences were found for the HC/AC ratio, especially in DM1 pregnancies. HC/AC growth trajectories of both macrosomic and non‐macrosomic fetuses differed from that of the controls, and the HC/AC ratio at term was lower in all diabetic subgroups except in non‐macrosomic DM2 cases. Conclusion We found altered (disproportionate) fetal growth in macrosomic and non‐macrosomic fetuses of women with DM1, DM2 and GDM. This indicates that the abnormal intrauterine environment affects the majority of these infants. Growth profiles differed among these groups, the most prominent growth deviations being found in the fetuses of women with DM1. The latter was most probably caused by poor glucose control. In monitoring fetal growth in diabetic pregnancies the HC/AC ratio should be used to assess altered fetal growth. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.